Instagram Sebagai Media Alternatif Merawat Gerakan Kolektif (Studi Kasus: Akun Instagram @ruanggulma) - Ustman, Widad Hafiyan; Indriati, Anisah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
This research is motivated by how Ruang Gulma makes Instagram as an alternative social media in conveying information and providing an autonomous alternative space that is easily accessible to the public. This is reinforced by the data of Instagram users in Indonesia which is increasing every year, as well as the features presented in Instagram in the form of photos and videos that are more dominant and more effective in their use in producing or consuming information. The author describes how Ruang Gulma then organizes its collective movement independently and maintains it to continue to exist by answering the problem of the crisis of alternative space in society, one of which is by using Instagram as a channel for organizing activities.